2021
DOI: 10.3389/fsoc.2021.689980
|View full text |Cite
|
Sign up to set email alerts
|

Men’s Attitude Towards Contraception and Sexuality, Women’s Empowerment, and Demand Satisfied for Family Planning in India

Abstract: Whilst the prevalence of unmet need and contraceptive use remained unchanged for 10 years (between 2005–2015) in India, gender restrictive norms and power imbalances also have persisted, preventing married women from meeting their family planning desires. Data for this study are from the 2015–6 National Family Household Survey, which contains information on fertility preferences and family planning for women in reproductive age. As a proxy for men’s attitudinal norms, we aggregated men’s perceptions regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…The current study showed that males who were divorced or separated had increased odds of involvement in FP decisions in Malawi, while males who were widowed were found to have increased odds of participation in FP decisions in Tanzania. A study carried out in Ethiopia [ 79 ] backed up this conclusion. This could be because joint decision-making between male and female partners to use contraception is a predisposing factor for male involvement in FP decisions among respondents who are married, cohabiting, widowed or divorced/separated.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The current study showed that males who were divorced or separated had increased odds of involvement in FP decisions in Malawi, while males who were widowed were found to have increased odds of participation in FP decisions in Tanzania. A study carried out in Ethiopia [ 79 ] backed up this conclusion. This could be because joint decision-making between male and female partners to use contraception is a predisposing factor for male involvement in FP decisions among respondents who are married, cohabiting, widowed or divorced/separated.…”
Section: Discussionmentioning
confidence: 93%
“…To achieve universal access to reproductive health care services, as part of the 2030 Agenda for Sustainable Development, it is crucial to increase access to contraception and ensure that the demand for FP is satisfied when utilizing effective contraceptive methods. Despite numerous coordinated efforts and success in increasing access to contraception, there are still significant obstacles to overcome [ 79 , 80 ]. Women’s empowerment, health, and gender equality are some of the related 17 SDGs goals/targets and the 2030 Agenda.…”
Section: Male Involvement In Family Planning and Its Implications For...mentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of women’s empowerment in the use of contraception should also be a concern for nutrition-sensitive value chains if the prevention of malnourishment is viewed from a more nuanced gendered lens rather than a simple sex disaggregation across nutritional outcomes. The inclusion of men and community leaders in gender-sensitive VCD projects must also be considered, as men’s and community leaders’ attitudes toward women’s empowerment and women’s reproductive choices impact women’s use of contraception and women’s agency in other areas of public health importance [ 78 , 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most patriarchal societies, men have dominated all decisions that pertains to family matters [27]. This male dominance has further exacerbated the vulnerability of women and girls affecting their access to health services.…”
Section: Discussionmentioning
confidence: 99%